Comparación del nivel socioeconómico entre la población del distrito de Punchana y San Juan Bautista del departamento de loreto periodo 2025 - Muro del Aguila, Kevinn Martin (2025)
The objective of the study is to compare the socioeconomic level of the population of the districts of Punchana and San Juan Bautista in the Department of Loreto, period 2025. The study is basic, descriptive, quantitative and retrospective, the design is non-experimental, descriptive comparative cross-sectional. The population is finite of 202,215 inhabitants, the type of sampling is probabilistic, stratified, the sample size is 383 distributed in the two districts, the technique was the survey, the instrument was the structured questionnaire, the data distribution was not normal, non-parametric hypothesis tests were used. The results of the socioeconomic level of the population of the Punchana district NSE A = 7%, NSE B = 45%, NSE C = 42%, NSE D = 4%, NSE E = 2%, in the district of San Juan NSE A = 6%, NSE B = 33%, NSE C = 30%, NSE D = 23%, NSE E = 7%. The highest level of education of the head of household and the predominant material of the dwelling floor are significantly different in the districts of Punchana and San Juan, however the affiliation of the head of household to the health system, the predominant material of the exterior walls of the dwellings and the type of sanitary service in the homes are not statistically significant differences, that is, it can be stated that the situation is similar in both districts. It is concluded that the district of Punchana shows a higher socioeconomic level and differs significantly between the districts of Punchana and San Juan Bautista (p = 0.000; average range Punchana = 225, San Juan Bautista = 172).